Monitoring of up to 15 years effects of lipoprotein apheresis on lipids, biomarkers of inflammation, and soluble endoglin in familial hypercholesterolemia patients - Víšek, J; Bláha, M; Bláha, V; Lášticová, M; Lánska, M; Andrýs, C; Tebbens, J Duintjer; Igreja E Sá, Ivone Cristina; Tripská, K; Vicen, M; Najmanová, I; Nachtigal, P (Orphanet journal of rare diseases, 2021)
BACKGROUND: Lipoprotein apheresis (LA) is considered as an add-on therapy for patients with familial hypercholesterolemia (FH). We aimed to analyze the data collected in the last 15 years from FH patients treated with LA, to elucidate the benefit of this procedure with respect to plasma lipids, biomarkers of inflammation, and endothelial dysfunction and soluble endoglin. RESULTS: 14 patients (10 heterozygous FH patients (HeFH), 4 homozygous FH patients (HoFH)) were treated by long-term lipoprotein apheresis. Lipid levels were examined, and ELISA detected biomarkers of inflammation and soluble endoglin. Paired tests were used for intergroup comparisons, and a linear regression model served to estimate the influence of the number of days patients were treated with LA on the studied parameters. LA treatment was associated with a significant decrease of total cholesterol (TC), LDL-C, HDL-C, and apoB, in both HeFH and HoFH patients, after single apheresis and in a long-term period during the monitored interval of 15 years. Biomarkers of inflammation and endothelial dysfunction were reduced for soluble endoglin, hsCRP, and MCP-1, and sP-selectin after each procedure in some HeFH and HoFH patients. CONCLUSIONS: LA treatment up to 15 years, reduced cholesterol levels, levels of biomarkers related to endothelial dysfunction, and inflammation not only after each procedure but also in the long-term evaluation in FH patients. We propose that long-term LA treatment improves lipid profile and endothelial dysfunction in familial hypercholesterolemia patients, suggesting a promising improvement in cardiovascular prognosis in most FH patients.
Keywords: separace krevních složek; Soluble endoglin; zánět; Lipoproteins; hyperlipoproteinemie typ II; Familial hypercholesterolemia; Lipids; biologické markery; Hyperlipoproteinemia Type II; lidé; endoglin; Inflammation; Endoglin; Humans; Biomarkers; Blood Component Removal; lipoproteiny; Lipoprotein apheresis